2012
DOI: 10.1016/j.jtcvs.2012.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless aortic valve replacement as an alternative treatment for patients belonging to the “gray zone” between transcatheter aortic valve implantation and conventional surgery: A propensity-matched, multicenter analysis

Abstract: This preliminary experience showed that, in patients at high risk for conventional surgery, SU-AVR is as safe and effective as TA-TAVI and that it is associated with a lower rate of postprocedural paravalvular leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 25 publications
2
83
4
2
Order By: Relevance
“…15,16 Sutureless AVR is reported to be an effective option for high-risk patients and can reduce the occurrence of paravalvular leakage compared to transcatheter AVR (TAVR). 17, 18 Considering the significant advantages of RTAVR, sutureless RTAVR can be an effective alternative with broad indications. Although RTAVR was initially introduced for patients without preoperative risk factors, the indications have been expanding and it can be an effective option for high-risk patients, as well as TAVR.…”
Section: Risk Factors For Length Of Icu and Hospital Stay In Miavrmentioning
confidence: 99%
“…15,16 Sutureless AVR is reported to be an effective option for high-risk patients and can reduce the occurrence of paravalvular leakage compared to transcatheter AVR (TAVR). 17, 18 Considering the significant advantages of RTAVR, sutureless RTAVR can be an effective alternative with broad indications. Although RTAVR was initially introduced for patients without preoperative risk factors, the indications have been expanding and it can be an effective option for high-risk patients, as well as TAVR.…”
Section: Risk Factors For Length Of Icu and Hospital Stay In Miavrmentioning
confidence: 99%
“…Smith et al [8] studied short-term outcomes, while Kodali et al [28] focused on long-term outcomes of patients who underwent TAVR. We also found 17 cohort studies [9,10,11,12,13,14,15,16,17,18,19,20,21,22,30,31,32] (table 2), among which 3 cohort studies reported no AKI event; 2 studies reported no AKI event in the TAVR group [30,31], and 1 study reported no AKI event in the SAVR group [32]. …”
Section: Resultsmentioning
confidence: 88%
“…We included 3 RCTs [5,7,8] and 14 cohort studies [9,10,11,12,13,14,15,16,17,18,19,20,21,22] with a total of 4,965 patients in the meta-analysis to assess the risk of AKI in patients undergoing TAVR. Of 14 cohort studies, 8 studies [10,11,13,14,16,17,19,22] used propensity score analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A propensity matched study between 519 patients having TAVR or sAVR using the Perceval S valve and then matched to 38 pairs has been presented by D'Onofrio. 21 Hemodynamic performance, complications, and pacemaker insertion rates were similar between the groups.…”
Section: Sutureless Valvesmentioning
confidence: 79%